Modernity on the Road Traffic of Surabaya in 1920s - Johny A Khusyairi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
This article explores the process and effects of modernization on the road traffic of Surabaya between 1920 and 1930 as reported by the newspapers. Two issues highlighted are the institutionalization of driver's license and traffic accidents. Besides newspapers, also used were films about the road traffic situation in Surabaya in the late 1920s. The modernization of the road of Surabaya implied social differences. People’s appreciation of modern vehicles was demonstrated by their ability to make use of the road modernly. Riding on modern vehicles did not always mean having modern behavior. Traffic accidents also proved the social differences. Interestingly, the two newspapers reported quite differently about the social differences on the modern road of Surabaya.